Cytomegalovirus viraemia is associated with poor growth and T-cell activation with an increased burden in HIV-exposed uninfected infants. - Garcia-Knight, M; Nduati, E; Hassan, A; Nkumama, I; Etyang, T; Hajj, N; Gambo, F; Odera, D; Berkley, J; Rowland-Jones, S; Urban, B (Lippincott, Williams & Wilkins, 2017)
Objective Factors associated with poor health in HIV-exposed-uninfected (HEU) infants are poorly defined.Wedescribe the prevalence and correlates of cytomegalovirus (CMV) viraemia in HEU and HIV-unexposed-uninfected (HUU) infants, and quantify associations with anthropometric, haematological, and immunological outcomes. Design Cross-sectional, including HEU and HUU infants from rural coastal Kenya. Methods Infants aged 2–8 months were studied. The primary outcome was CMV viraemia and viral load, determined by quantitative PCR. Correlates were tested by logistic and linear regression; coefficients were used to describe associations between CMV viraemia and clinical/immunological parameters. Results In total, 42 of 65 (64.6%) infants had CMV viraemia [median viral load, 3.0 (interquartile ranges: 2.7–3.5) log10 IU/ml]. Compared to community controls, HEU infants had six-fold increased odds of being viraemic (adjusted odds ratio 5.95 [95% confidence interval: 1.82–19.36], P=0.003). Age, but not HEU/HUU status, was a strong correlate of CMV viral load (coefficient=-0.15, P=0.009). CMV viral load associated negatively with weight-for-age (WAZ) Z-score (coefficient= -1.06, P=0.008) and head circumference-for-age Z-score (coefficient= -1.47, P=0.012) and positively with CD8þ T-cell coexpression of CD38/human leucocyte antigen DR (coefficient=15.05, P=0.003). Conclusion The odds of having CMV viraemia was six-fold greater in HEU than HUU infants when adjusted for age. CMV viral load was associated with adverse growth and heightened CD8þ T-cell immune activation. Longitudinal assessments of the clinical effects of primary CMV infection and associated immunomodulation in early life in HEU and HUU populations are warranted.